Newly onset: Sudden & severe headache in a patient who overused analgesic - Khairi, Che Mat; Rohayah, Husain; Nasir, Mohamad (Ibn Sina Trust, 2015)
This case report presented a rare cause of severe headache in a patient who developed episodes of acute severe headache for the first time. The earliest accurate provisional diagnosis is crucial for a new onset severe headache in adult. A good history taking and high index of suspicious are remained the most important clinical component in managing severe first time headache in adult. The differential diagnosis of subarachnoid hemorrhage, space-occupying lesion with increased intracranial pressure, acute intoxication, meningoencephalitis and others must be ruled out as these conditions are benefited in early management. In this patient, progressive development of headache is masked by severe intense headache, which later will be described as acute headache. The causes of newly onset severe intense headache will be discussed in the discussion.